Menumbuhkan Minat Dan Jiwa Berwirausaha Yang Mandiri Di SMK Mayjend Sutoyo SM Medan - Nanda, Ananda Fitriani Dewi; Jumeida Simatupang; Yulia Sari (LPPM Universitas Potensi Utama, 2023)
Vocational High School (SMK) aims to produce graduates who are ready to enter the workforce independently as entrepreneurs (entrepreneurs). For this reason, entrepreneurial characteristics in vocational schools need to be conditioned both through intra-curricular, co-curricular and extra-curricular activities. The application of entrepreneurial character in SMK can be done through learning activities. The method is carried out in the classroom using slides and presentations in front of the room. Based on questions and answers and direct observation during the activity, this community service activity yielded the following results: Students at SMK Mayjend Sutoyo SM Medan understand the interest and spirit of entrepreneurship to become strong entrepreneurs. Several factors that support the implementation of this community service activity are the amount of interest and enthusiasm of the participants during the activity, so that the activity takes place smoothly and effectively. Based on the analysis of the results of the activity, several things can be concluded, such as: knowledge and understanding of students about the interest and spirit of entrepreneurship at SMK Mayjend Sutoyo SM Medan as a solution to giving birth to strong entrepreneurs.